Penerapan Model Pengelolaan Kelas Melalui Pendekatan Proses Kelompok untuk Meningkatkan Sikap Disiplin dan Motivasi Belajar pada Siswa Kelas IV Sekolah Dasar - Mulia, Novia Sri; Hanifah, Nurdinah; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2019)
Based on the problems that occur regarding discipline and learning motivation in the fourth grade students of SDN Nanggerang, Cisitu District, Sumedang Regency, the effort that can be made to correct the problem is applied a class management model through a group process approach. These problems were corrected through Classroom Action Research (CAR) with the design of the Kemmis and Taggart model consist of the stages of planning, implementation, observation, and reflection. The instruments used in the study included teacher performance observation guidelines for the planning and implementation stages of learning, observation guidelines for student disciplinary attitudes, student learning motivation questionnaires, and field notes of teacher performance and student activities. This research was completed in three cycles. The results of the research on planning cycle I reached 87,5%, cycles II 91,67%, cycle III increased to 96% and reached the target. Then, in the implementation of the first cycle reached 87,5%, the second cycle increased to 94%, and the last cycle III reached 98,43% and had reached the target. Furthermore, the discipline attitude of students in the first cycle reached 68,57%, cycles II 73,57%, then cycle III increased and reached the target of 80,11%. For the questionnaire student learning motivation in the first cycle reached 74,47%, the second cycle was 76%, and the third cycle reached the target of 81,06%. Therefor, this study succeeded increas the discipline attitude and motivation of learning on the fourth grade students of SDN Nanggerang, Cisitu District, Sumedang Regency.